2020
DOI: 10.1080/1478422x.2020.1742409
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of oxide layers on zirconium alloys using 18O tracers

Abstract: In this work, samples of zirconium alloys Zr1Nb and Zircaloy-4W were subjected to two-stage oxidation experimentsat first in H 2 16 O solution and then in H 2 18 O steam. Raman spectroscopy was used to analyse distribution of 18 O isotope in corrosion layers of the alloys. Layered distribution of 18 O was observed in case of Zr1Nb samples; Zircaloy-4W had 18 O present only at metal/oxide interface. This observation is attributed to differing kinetic transitions, which influence transport of oxygen through oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Some researchers suggest that the initial stage of corrosion results in the formation of a compact t-ZrO 2 oxide film, and as the thickness of the oxide film increases, the compressive stress in the outer oxide film gradually diminishes, leading to a gradual transformation of t-ZrO 2 into loose m-ZrO 2 . The phase transformation in the oxide film can induce cracks and other defects, thereby accelerating zirconium alloy corrosion [39][40][41]. Based on our findings, it can be concluded that hydrogenation has little effect on the t-ZrO 2 phase content in the oxide film, and there is no direct correspondence between the t-ZrO 2 content and the corrosion resistance of Zircaloy-4 in 360 • C/18.6 Mpa/Li + B aqueous solution samples corroded for 70 days is presented in Figure 11 and Table 1.…”
Section: Raman Spectroscopy Analysis Of the Oxide Filmmentioning
confidence: 99%
“…Some researchers suggest that the initial stage of corrosion results in the formation of a compact t-ZrO 2 oxide film, and as the thickness of the oxide film increases, the compressive stress in the outer oxide film gradually diminishes, leading to a gradual transformation of t-ZrO 2 into loose m-ZrO 2 . The phase transformation in the oxide film can induce cracks and other defects, thereby accelerating zirconium alloy corrosion [39][40][41]. Based on our findings, it can be concluded that hydrogenation has little effect on the t-ZrO 2 phase content in the oxide film, and there is no direct correspondence between the t-ZrO 2 content and the corrosion resistance of Zircaloy-4 in 360 • C/18.6 Mpa/Li + B aqueous solution samples corroded for 70 days is presented in Figure 11 and Table 1.…”
Section: Raman Spectroscopy Analysis Of the Oxide Filmmentioning
confidence: 99%